The influence of advertisements and religious factors on condom use intentions among married male Muslims in Pakistan - Madni, Abdul Rehman (2017)
Despite government measures to control birth rate in Pakistan and spreading awareness about family planning through advertisements, Pakistani population growth rate is still high. In Pakistan, advertisements of contraceptives are cursed because advertisements are labeled as indecent, immoral, anti-cultural and anti-religion. For instance, Pakistan Electronic Media Regulatory Authority (PEMRA) banned advertisements of “Josh condom” because of the complaints and pressure of the Pakistani people as they argued that the advertisements disregard to their religious values. However, facts revealed that Josh condom sale recorded a sharp increase after the ban of the advertisements. The main objective of this study is to investigate the influence of condom advertisements on attitude toward advertisements of condoms (AtAc) and behavioral intentions of Pakistani married male Muslims to use condoms (BI). Religious factors namely religious beliefs (RB), religious leaders (RL), religiosity (REL) and subjective norms (SN) were also incorporated into the study because of their relevancy in an advertising context. The mediating role of AtAc and the moderating role of REL was also the focus of the study. Data were collected from the Pakistani married male Muslims using a cross-sectional study design. The study adopted snowball sampling and gathered data from 213 respondents through the personally-administered method. Partial Least Squares-Structural Equation Modeling (PLS-SEM) was used to test the study hypotheses. Findings of the study show that PF, RB, SN, and AtAc are important factors in influencing condom use intentions of Pakistani married male Muslims. Results also revealed that AtAc significantly mediates between the relationship of PF and BI and religiosity significantly moderates between the relationship of PF, RL, and BI. Conclusively, this research has added valuable contributions, both practically and theoretically in the advertising field. It also contributed to the Theory of Planned Behavior by adding variables which are significant in determining the behavioral intention. It is also beneficial for those who want to advertise products especially controversial products in Pakistani media